GAMBARAN SELF AWARENESS TENTANG TINDAKAN VULVA HYGIENE PADA WANITA DEWASA DALAM MENCEGAH INFEKSI SALURAN KEMIH - Santi Fitri Yani; Maria Yunita Indriarini; Linda Sari Barus (Jurnal Kesehatan, 2022)
The incidence of Urinary Tract Infection in Indonesia ranks second which often attacks women's health. The preliminary study found that 1 out of 18 female students had urinary tract infections with four recurring events. The research objective was to describe self awareness about vulva hygiene measures in adult women in preventing urinary tract infections. Self awareness is a person's intelligence in placing himself in certain situations and conditions and what he should do. This research uses quantitative methods. The sampling technique used was proportionate stratified random sampling with 195 female students as respondents. The instrument uses a google form questionnaire that has been tested for validity and reliability. The results showed that 137 respondents (70.2%) had high self-awareness to recognize feelings and behaviors, 190 respondents (97.5%) had high self-awareness to recognize strengths and weaknesses, 162 respondents (83.1%) had self-awareness have high self-awareness, 108 respondents (55.4%) have high self-awareness of making the right decisions, 170 respondents (87.2%) have self-awareness skilled at expressing thoughts, feelings, opinions, and high beliefs, 112 respondents (57.5 %) have moderate self-awareness in self-evaluating. The conclusion of the study is that most of the adult women's self-awareness is high regarding vulva hygiene measures in preventing urinary tract infections. The researcher suggests further researchers to be able to find other variables related to vulva hygiene measures in preventing urinary tract infections.